On the Relationship between Partial Molar Excess Gibbs Energy and Contact Angle - M. C. Harris (International Mineral Processing Congress, 2018)
"In the flotation process the contact angle is an important indicator of the hydrophobicity of a mineral particle. There is considerable literature showing that the contact angle increases when the chain length of the alkyl group associated with the collector molecule used to render the valuable mineral particle hydrophobic increases. The extent to which an alkyl group interacts with surrounding water molecules is quantified thermodynamically by the excess Gibbs energy. In the present paper it is shown that there exists generally a strong linear relationship between the excess Gibbs energy of the alkyl group associated with the collector and the contact angle. The structure-activity of such alkyl groups is in turn related to the total surface area, molecular volume, the molar volume, molecular weight of the functional groups in the molecule and interaction energies. It is proposed that the demonstrated relationship is indicative of the role which the alkyl group component of the collector, which is attached to the mineral particle, plays in increasing the extent to which water molecules at the surface of the mineral are rejected from the surface thus increasing the contact angle. The relationship between excess Gibbs energy and surface tension is further explored with a view to relating the observations quantitatively to the parameters in the Young equation.INTRODUCTIONThe issue of wettability of materials is of great importance to many industrial applications. Wettability studies usually involve the measurement of contact angles which indicate the degree of wetting when a solid and liquid interact. As is well known the contact angle (O) is the angle between planes tangent to the surfaces of the solid and the liquid at the wetting perimeter which is the zone where the air, water and solid phase merge. When the air bubble attaches to the solid surface there is an increase in the air/solid interface area and a decrease in the solid/water interface area. For attachment to occur the cosine of the contact angle should be less than 1 and this will be promoted if the interfacial surface tension between the air and the solid (? SV) is low. Classically the relationship between these parameters has been expressed through the Young equation (1) for a perfectly flat surface:"